(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
This article examines the theory and history of the formation of Islamic values in Uzbekistan, which has witnessed the integration of various cultures and religions throughout its rich past. The article examines the early conquests of Islam, the gradual spread of Islam, the establishment of Islamic empires, the influence of Sufism, and the enduring legacy of Islam in Uzbekistan. This article examines the historical context and key events to shed light on the profound impact of Islam on the culture, values, society, and identity of the Uzbek people.